#CanadaPerforms: How it Came to Be and What We Learned About Building Virtual Communities - Chan, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Kevin Chan is Director of Public Policy, Canada for Facebook. In this piece, he describes the origins of the #CanadaPerforms series, a partnership between Facebook Canada and the National Arts Centre that presented over seven hundred livestreamed musical performances by Canadian musicians during the pandemic.